Rule 2.1 of Ontario’s Rules of Civil Procedure: Responding to Vexatious Litigation While Advancing Access to Justice? - Kennedy, Gerrard J. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2018)
This article analyzes the first three years of the operation of Rule 2.1 of Ontario’s Rules of Civil Procedure (the “Rule”), which allows a court to very summarily dismiss litigation that is “on its face” frivolous, vexatious, and/or abusive. The author explores the history of and rationale for the Rule, in the context of the access to justice crisis in Ontario, and in light of the perceived inadequacy of alternative mechanisms for addressing the dangers raised by vexatious litigants. He then reviews all 190 Rule 2.1 decisions decided between July 1, 2014 and June 30, 2017, with the goal to provide guidance for future lawyers and judges considering using the Rule. This is followed by an analysis of the effects on access to justice of the Rule, in terms of providing speedy and cost-efficient resolution of actions on their merits. The author concludes by considering how the Rule should be used in the future – doctrinally, institutionally, and ethically. His conclusions are hopeful. The Rule is powerful, and its use should prompt some pause in judges and lawyers. By and large, however, the Rule has been very well employed. It has resulted in immense savings of time and financial expense and many cases model fairness to vulnerable parties. In rare instances where the Rule’s (attempted) use has been inappropriate, costs in terms of delay and financial expense are usually minimal. The Rule is ultimately an inspiring example of how civil procedure can be amended to facilitate access to justice.